2007
DOI: 10.1038/ismej.2007.77
|View full text |Cite
|
Sign up to set email alerts
|

The diversity of the bacterial communities associated with the azooxanthellate hexacoral Cirrhipathes lutkeni

Abstract: This study examined the symbiotic microbiota of the hexacoral Cirrhipathes lutkeni using traditional plate culture, fluorescence in situ hybridization (FISH) and 16S rDNA characterization. FISH counts for the whole coral (holobiont) showed a major presence of c-Proteobacteria (22%) and Actinobacteria (19%), followed by a-Proteobacteria (14%), Firmicutes (9%), Cytophaga-Flavobacterium (7%), b-Proteobacteria (6%) and Chloroflexi (2%). In contrast to the diversity observed by FISH, plate cultures were found to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
24
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 23 publications
(46 reference statements)
6
24
0
Order By: Relevance
“…The predominant Bacteria phylum in both healthy and affected corals was Proteobacteria, consistent with previous observations based on culture-independent methods in other reef-building corals (Santiago-Vazquez et al, 2007;Kvennefors et al, 2010). Yet, a shift in the relative sequence abundance of the Proteobacteria classes was strongly associated to the disease in the two coral species.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The predominant Bacteria phylum in both healthy and affected corals was Proteobacteria, consistent with previous observations based on culture-independent methods in other reef-building corals (Santiago-Vazquez et al, 2007;Kvennefors et al, 2010). Yet, a shift in the relative sequence abundance of the Proteobacteria classes was strongly associated to the disease in the two coral species.…”
Section: Discussionsupporting
confidence: 79%
“…In S. siderea the Chao1 index was higher in the healthy samples, whereas in D. strigosa the index was higher in the affected sample. This indicates that variations in those parameters are heavily dependent upon the basal community composition specific for each coral species, and are not a reflection of the disease condition.The predominant Bacteria phylum in both healthy and affected corals was Proteobacteria, consistent with previous observations based on culture-independent methods in other reef-building corals (Santiago-Vazquez et al, 2007;Kvennefors et al, 2010). Yet, a shift in the relative sequence abundance of the Proteobacteria classes was strongly associated to the disease in the two coral species.…”
supporting
confidence: 79%
“…However, we are only just starting to investigate and understand the forces that govern their patterns of diversity, distribution and role in the coral holobiont ecosystem. Bacteria, archaea and viruses are ubiquitous in the marine system, and thrive in coral reef waters (Sorokin, 1973;Dinsdale et al, 2008), but these communities have been shown to be distinct from those associated with the coral animal (Rohwer et al, 2001(Rohwer et al, , 2002Cooney et al, 2002;Frias-Lopez et al, 2002;Guppy and Bythell, 2006;Santiago-Vazquez et al, 2007;Kvennefors et al, 2010;Sunagawa et al, 2010;Chen et al, 2011;Tremblay et al, 2011;Ceh et al, 2012;Schö ttner et al, 2012), suggesting that there is specific control of the microbiomes (associated bacterial and archaeal communities), by either biological or microenvironmental factors influenced by the host.…”
Section: Introductionmentioning
confidence: 99%
“…Community fingerprinting methods, such as denaturing gradient gel electrophoresis (DGGE) and T-RFLP, allow for comparisons of many different replicates or samples to answer ecological questions concerning both the membership and stability of microbial communities. To understand the physical distribution and abundance of these microbial communities direct observations are required; fluorescence in situ hybridization (FISH) has been applied to study the bacterial communities associated with a number of marine hosts including sponges, corals and ascidians (Ainsworth et al, 2006;Hoffmann et al, 2006;Martinez-Garcia et al, 2007;Santiago-Vazquez et al, 2007;Neulinger et al, 2009), as well as to study the bacteria causing gall formation in the marine red algal genus Prionitis (Ashen and Goff, 2000). Wherever the application of FISH directly to algae is difficult because of intense background autofluorescence from algal cells, we previously successfully developed a catalyzed reporter deposition or catalyzed reporter depositionfluorescence in situ hybridization (CARD-FISH) protocol to study the surface bacterial community of several marine macroalgae (Tujula et al, 2006).…”
Section: Introductionmentioning
confidence: 99%